Mechanical strain stimulates COPII‐dependent secretory trafficking via Rac1. (8th August 2022) - Phuyal, Santosh; Djaerff, Elena; Le Roux, Anabel‐Lise; Baker, Martin J; Fankhauser, Daniela; Mahdizadeh, Sayyed Jalil; Reiterer, Veronika; Parizadeh, Amirabbas; Felder, Edward; Kahlhofer, Jennifer C; Teis, David; Kazanietz, Marcelo G; et al.
Abstract: Cells are constantly exposed to various chemical and physical stimuli. While much has been learned about the biochemical factors that regulate secretory trafficking from the endoplasmic reticulum (ER), much less is known about whether and how this trafficking is subject to regulation by mechanical signals. Here, we show that subjecting cells to mechanical strain both induces the formation of ER exit sites (ERES) and accelerates ER‐to‐Golgi trafficking. We found that cells with impaired ERES function were less capable of expanding their surface area when placed under mechanical stress and were more prone to develop plasma membrane defects when subjected to stretching. Thus, coupling of ERES function to mechanotransduction appears to confer resistance of cells to mechanical stress. Furthermore, we show that the coupling of mechanotransduction to ERES formation was mediated via a previously unappreciated ER‐localized pool of the small GTPase Rac1. Mechanistically, we show that Rac1 interacts with the small GTPase Sar1 to drive budding of COPII carriers and stimulates ER‐to‐Golgi transport. This interaction therefore represents an unprecedented link between mechanical strain and export from the ER. Synopsis: Whether and how mechanical signals regulate the endoplasmic reticulum (ER) is incompletely understood. Here, mechanical stress is found to increase ER exit site (ERES) numbers and secretory trafficking to respond with surface expansion. Mechanotransduction to ERES involves the small GTPase Rac1. Rac1 localizes to the ER where it forms a complex with Sar1. Rac1 stimulates the formation of COPII carriers. Blocking ERES renders cells more sensitive to mechanical strain. Abstract : Mechanical strain regulates the number of endoplasmic reticulum exit sites through small GTPase heterodimerization.